Structural and microstructural tailoring of rare earth sesquioxides by swift heavy ion irradiation. Issue 11 (1st August 2016) - Sattonnay, G.; Bilgen, S.; Thomé, L.; Grygiel, C.; Monnet, I.; Plantevin, O.; Huet, C.; Miro, S.; Simon, P.
Abstract : The structural transformations induced in Gd2 O3 and Eu2 O3 irradiated with high‐energy ions (94‐MeV Pb and 1042‐MeV Xe), where ionization processes (electronic stopping) dominate the ion slowing‐down, have been studied via the combination of XRD and Raman experiments. Irradiation induces a cubic‐to‐monoclinic phase transformation; the radiation‐induced monoclinic phase shows strong preferential orientation. This structural modification is accompanied by changes in the photoluminescence properties of sesquioxides. The results show that swift heavy ion irradiation is a powerful tool to control the properties of oxides at the nanoscale.